Diversity in school and new requirements for teaching work - Gustavo Bruno Bicalho Gonçalves (Universidade Federal de Santa Maria, 2013)
This article begins with a discussion of the principles of social justice and school justice that underlies public policies for diversity in schools, and it examines the stated goal that aims at contributing to promotion of equality. Based on statements provided by the teachers participating in the second phase of the research project "Teaching Work in Basic Education in Brazil", we analyze the effects of these policies as expressed in the contradiction experienced by teachers at work, when they try to adapt the principle of equality to the attention to diversity. We observe that this contradiction leads to new workloads and makes it difficult for teachers to find meaning in their work.